Ochrona dróg oddechowych przed zagrożeniami biologicznymi – zmiana paradygmatu wobec masywnej transmisji SARS-CoV-2 - Aleksander Michalski; Agata Bielawska-Drózd; Jarosław Pinkas; Janusz Kocik (Wiedza Medyczna, 2020)
Currently observed intensive spread of COVID-19 suggests the virus may be more airborne than previously assumed and may be also spread by air/aerosol, not only by droplet, at a distance greater than the recommended as safe. The paper presents current recommendations and arguments indicating the importance of respiratory protection during COVID-19 pandemic. The use of certified respirators allows the protection of critical human resources and more effective protection of medical personnel. The widespread and skillful use of improvised personal face coverings along with other elements of the sanitary regime (isolation, hand hygiene) allows achieving a synergistic effect of limiting the spread of the virus in society.